Kajian Pengelolaan Dan Pengawasan Bantuan Dana Operasional Sekolah - Shelty Deity Meity Sumual; Suiling Pontoh; Maria Wihelmina Kaparang; Victor Nomel Kumajas (Journal on Education, 2024)
Education is an important aspect in country development. Therefore, funding for education is very vital to ensure equal access and quality of education for the entire community. Education financing is regulated by regulations, including Government Regulation no. 48 of 2008. Collaboration between the government, regional government and the community is important to create a quality education system. School Operational Assistance Funds (BOS) support school operational needs, relieve disadvantaged students from operational costs, and reduce educational participation gaps. This research was conducted with the aim of understanding in depth the practices of managing and supervising BOS funds in schools. The method applied in this research is a qualitative literature study method. The research results show that management of BOS funds needs to be carried out in accordance with the principles including transparency, accountability, effectiveness and efficiency, self-management and participation, as well as democracy and mutual trust. Supervision is carried out by a team of central government auditors by reviewing recapitulations and school accountability reports.